Aggressive management of doxorubicin-induced cardiomyopathy associated with 'low' doses of doxorubicin. Issue 828 (October 1994) - Sriskandan, S.; O'Brien, M. E.; Smith, I. E.; Collins, P.; Gore, M. E.
Abstract : There is a dose-effect relationship between doxorubicin and the incidence of symptomatic cardiac failure. It is generally thought that doses below 500-550 mg/m2 are safe but, when objective measures of cardiac function are used, it becomes apparent that degrees of cardiac failure occur at doses below this. We present here the case histories of two patients who developed very severe cardiac failure at cumulative doses well below 500 mg/m2 but who survived their initial cardiac illness due to aggressive intervention. In one case, the patient was successfully treated by orthotopic cardiac transplantation.